“Caminhos d'agente": curso em saúde mental para agentes comunitátios de saúde do município de Sobral/CE - ARAÚJO, Denise da Silva (2023)
This work presents a mental health training course for a group of Community Health Agents in the municipality of Sobral/CE, linked to the Professional Postgraduate Programme in Psychology and Public Policy of the UFC, Sobral Campus. Thirty-one Community Health Agents participated in the course, 24 cis women and 7 cis men, between the ages of 22 and 57, who work in 20 Basic Health Units distributed between the Sobral headquarters and the districts. The "Caminhos D'Agente" course was divided into two modules, one on mental health and the other on aging. The course took place face-to-face in Sobral over 8 days in August 2023 and resulted in a 40-hour certificate issued by the Federal University of Ceará. All 31 participants attended the sessions regularly, so they all received the certificates. The course is part of a study approved by the Research Ethics Committee under opinion number 6.081.292. The meetings were recorded and transcribed, with the consent of the participants, and organized according to the stages of the methodology used. In addition, information was collected using a socio-demographic questionnaire and questionnaires evaluating the interventions on each day. The course and information analysis stage followed Maguerez's Arc problematizing methodology. It became evident that the identification of demands for mental health care was initially guided by intuitive rather than conceptual questions, influenced by a nosographic perspective, and relied heavily on medication as the primary therapeutic strategy. During the course, the CHWs discussed their conceptions of mental health and psychological suffering, medicalization, teamwork and networking, the use of soft health technologies, issues affecting mental health care in various care spaces, and the subjective impacts of CHWs' work overload. Upon finishing the course, a setting to encourage continuous health education was established, empowering professionals to cultivate their self-awareness, navigate their personal and professional lives, understand their roles within the team, interact with patients and families, and combat the negative connotations surrounding psychological suffering.